THE RELATIONSHIP OF SOME PHYSICAL MEASUREMENTS TO THE DISTINCTIVE STRENGTH, SPEED, AND ACHIEVEMENT OF YOUNG LONG JUMPERS - Khaleel mohmmed, Abbas; Hasan Jawir, Laith; Abdulameer Hussein, Ali (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
There is no doubt that the scientific progress that is taking place in most fields, especially the field of sports, has witnessed a significant and noticeable development in recent times in various sports, achieving a qualitative leap in achieving very high achievements in some sports, specifically athletics, and that today we are in dire need of More giving to achieve a bright future that guarantees broad scientific progress and development for the sport of athletics and its various competitions. Strength, which is characterized by speed, plays a major role in most athletics competitions and is of great importance for motor notes, which result from the link between muscular strength and speed to produce a good harmonious movement pattern. The current research aimed to identify the relationship between height and strength characterized by speed among long young jumpers. The researcher assumed the existence of a significant correlation between height and strength characterized by speed and achievement among long jumpers. The researchers adopted the descriptive survey method because it is the closest research method to solving the research problem by the scientific method, as the method is one of the main and basic methods in research. The research population was players from the Middle Euphrates clubs, and the research sample was long jump players, and they divided into two groups, the first of which was players whose height exceeded (180) cm, and the second was players whose height was less than (171) cm. The researchers reached the most important conclusions, which is that there is a significant relationship between height. The long jump and achievement. The most important recommendations made by the researchers was the preference for choosing players with long bodies, especially the lower extremities, for many competitions, especially jumping and jumping competitions. Strength, characterized by speed, is considered one of the physical abilities that has a strong impact on movements, as it combines two basic characteristics and plays an important role in achieving sporting achievements.